2018
DOI: 10.1108/maj-02-2018-1804
|View full text |Cite
|
Sign up to set email alerts
|

Cyber security assurance process from the internal audit perspective

Abstract: Purpose The purpose of this study is to analyze the cybersecurity assurance approaches to determine the key issues and weaknesses within the internal audit and risk management perspective. Organizations increasingly rely on digital data to drive their growth and they are interconnected in a complex web to a multitude of stakeholders. Design/methodology/approach In this paper, cybersecurity is defined, and cybersecurity assurance model is explained based on the relevant literature. In addition, the role of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 7 publications
0
39
0
Order By: Relevance
“…The authors find that the association with forecast accuracy appears to be strongest for IT control weaknesses most directly related to data processing integrity Steinbart et al, 2012 The relationship between internal audit and information security Exploratory study. Steinbart et al, stated that the internal audit and information-security functions should co-operate synergistically (continued) Kahyaoglu and Caliyurt, 2018 Cyber security assurance process from the internal audit perspective Conceptual study. The authors concluded that cyber-risk must be managed and stated that it is very important to maintain formal documentation on related cyber controls and internal audit should be an integral part of cybersecurity assurance process, as internal audits have a unique capacity to look across organizations The role of internal audit and user training in information-security policy compliance Qualitative case analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors find that the association with forecast accuracy appears to be strongest for IT control weaknesses most directly related to data processing integrity Steinbart et al, 2012 The relationship between internal audit and information security Exploratory study. Steinbart et al, stated that the internal audit and information-security functions should co-operate synergistically (continued) Kahyaoglu and Caliyurt, 2018 Cyber security assurance process from the internal audit perspective Conceptual study. The authors concluded that cyber-risk must be managed and stated that it is very important to maintain formal documentation on related cyber controls and internal audit should be an integral part of cybersecurity assurance process, as internal audits have a unique capacity to look across organizations The role of internal audit and user training in information-security policy compliance Qualitative case analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In related work, Kahyaoglu and Caliyurt (2018) examined the cybersecurity assurance process from the internal audit perspective. They developed a model to introduce the way in which the internal audit and information-security functions could work together to support organizations in accomplishing a cost-effective level of information security.…”
Section: Cybersecuritymentioning
confidence: 99%
See 1 more Smart Citation
“…Digitalisation raises questions about the evolution of internal audit activities, which comes with a certain degree of complexity and uncertainty for organisations (Schoemaker et al, 2018). The digitalisation of the business environment makes business processes more complex (Nuijten et al, 2015) and people are increasingly using digital devices, networks and cloud computing (Kahyaoglu and Caliyurt, 2018). This environment, where big data are continuously generated and new technologies constantly emerge, is increasingly interconnected with organisational systems (Appelbaum et al, 2017;Flora and Rai, 2015).…”
Section: Internal Audit Rolementioning
confidence: 99%
“…However, although some internal auditors can be torn between the added value of consulting activities for management and the preservation of their independence, they still perform consulting activities to bring additional value to organisations (Betti and Sarens, 2020). For example, internal auditors could play a more proactive role in the early stages of implementing new IT developments (Kahyaoglu and Caliyurt, 2018) or when implementing new technologies (Flora and Rai, 2015). Internal auditors could also provide advice and insight on cybersecurity programmes and risk prevention (Dixon and Singer, 2011;Kahyaoglu and Caliyurt, 2018), thereby performing more consulting activities.…”
Section: Internal Audit Rolementioning
confidence: 99%